Analisis Pembelajaran Bahasa Arab pada Kanal Youtube "Arab Podcasts" Berdasarkan Perspektif Filsafat Perenialisme - Suhaeni Rahmawati; Wahyudin, Dedy; Oemar Hasyim, Pareza (Jurnal Al-Maqoyis, 2025)
This article aims to describe Arabic language learning on the YouTube channel “Arab Podcasts” based on the perspective of perennialism philosophy. This research used qualitative approach and descriptive method. Primary data sources come from Arabic language learning videos on the “Arab Podcasts” YouTube channel, while the secondary data sources come from books, scientific articles, and documents that are related to the perennialism philosophy. The data collection technique is based on listening and note-taking method. The data analysis technique used consists of three stages including data reduction, data display, and conclusion drawing. The result of this study is the discovery of conformity between the concept of Arabic language learning on the YouTube channel “ Arab Podcasts ” with the learning principles of perennialism philosophy.